Synthesis of positively and negatively charged silver nanoparticles and their deposition on the surface of titanium; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Sharonova A. A. Anna Aleksandrovna; Loza K.; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Prymak O.; Epple M. (2016, 2016)
Title screen